Postoperative alterations of sagittal cervical alignment and risk factors for cervical kyphosis in 124 Lenke 1 adolescent idiopathic scoliosis patients - Junyu Li (BMC, 2021)
Abstract Background This study aims to analyze postoperative changes of cervical sagittal curvature and to identify independent risk factors for cervical kyphosis in Lenke type 1 adolescent idiopathic scoliosis (AIS) patients. Methods A total of 124 AIS patients who received all-pedicle-screw instrumentation were enrolled. All patients were followed up for at least 2 years. The following parameters were measured preoperatively, immediately after the operation, and at the last follow-up: pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), lumbar lordosis (LL), thoracic kyphosis (TK), global thoracic kyphosis (GTK), proximal thoracic kyphosis (PrTK), T1-slope, cervical lordosis (CL), McGregor slope (McGS), sagittal vertical axis (SVA), C2–7 SVA (cSVA), and main thoracic angle (MTA). Statistical analysis was performed to evaluate postoperative alterations of and correlations between the parameters and to identify risk factors for cervical kyphosis. Statistical significance was set at P < 0.05. Results After the operation, PrTK and T1-slope significantly increased (3.01 ± 11.46, 3.8 ± 10.76, respectively), cervical lordosis improved with an insignificant increase (− 2.11 ± 13.47, P = 0.154), and MTA, SS, and LL decreased significantly (− 33.68 ± 15.35, − 2.98 ± 8.41, 2.82 ± 9.92, respectively). Intergroup comparison and logistic regression revealed that preoperative CK > 2.35° and immediate postoperative GTK < 27.15° were independent risk factors for final cervical kyphosis, and △T1-slope < 4.8° for a kyphotic trend. Conclusions Postoperative restoration of thoracic kyphosis, especially proximal thoracic kyphosis, and T1-slope play a central role in cervical sagittal compensation. Preoperative CK, postoperative small GTK, and insufficient △T1-slope are all independent risk factors for cervical decompensation.